Capercaillie in the Alps: genetic evidence of metapopulation structure and population decline - Segelbacher, Gernot; Storch, Ilse (Molecular ecology, 2002)
In the Alps, the capercaillie is distributed in a metapopulation pattern with local populations on mountain ranges separated by farmland valleys. Habitat deterioration, primarily related to human land use, resulted in population declines and range contractions became obvious. At the edge of a species’ range, lower connectivity and less gene flow may render populations more susceptible to decline and extinction than in the core of the range. If this were true for the capercaillie in the Alps, edge populations should be subject to limited gene flow and should show genetic signs of a more severe population decline than core populations. To test this hypothesis, we used microsatellite DNA typing techniques. We assessed genetic variation within and among 18 local capercaillie populations across the Alps in relation to geographical distribution within the metapopulation system. All populations showed high levels of genetic variation in terms of average number of alleles, allelic richness and heterozygosity. Excess heterozygosity suggested a recent population decline, that was more pronounced in edge than core populations. We found high gene flow, but also significant differentiation among populations. Differentiation among edge populations was related to geographical distance, and appeared to be a recent process, most probably caused by reduced gene flow after population decline. In the core group, the high mountains of the central Alps seem to limit dispersal, and genetic drift was the most likely explanation for the observed differentiation among populations. We conclude that maintaining connectivity within the metapopulation system is vital for capercaillie conservation in the Alps.